Requirements for transforming Taif University into a green university in light of the experiences of the universities of Wageningen in the Netherlands, Harvard and California Berkeley in the Americas - Al-Hosiny, Hatim Abdullah (Journal of Educational and Psychological Sciences, 2025)
This research aims to identify the requirements for transforming Taif University into a green university in light of the experiences of Wageningen University in the Netherlands, Harvard University in the United States of America, and the University of California Berkeley. To address the research problem, the descriptive analytical documentary approach was used. The tool was represented by documents and studies that dealt with the green university during the years 2020-2024. The research consisted of an introduction and three chapters; the first dealt with: the concept of green universities, their importance, objectives, justifications, and dimensions. The second included the experiences of Wageningen University in the Netherlands, Harvard University in the United States of America, and the University of California Berkeley, and the requirements for transforming into green universities. The third was devoted to presenting the reality of implementing green universities in the Kingdom of Saudi Arabia. The research concluded with a conclusion that included a proposed vision for transforming Taif University into a green university in light of the experiences of the universities under study, including the starting points of the proposed vision, its objectives, and the requirements for achieving it, in addition to concluding recommendations and proposals for complementary studies on the subject.
Keywords: Requirements; Green University; Wageningen University; Harvard University; University of California Berkeley